Occupational health hazard among Security Guards in Kathmandu District, Nepal - Naresh Manandhar; Archana Jha; Aakash Mishra; Anjali Mishra; Vaibhav Gupta; Tara Baniya; Sunil Kumar Joshi (Occupational Health and Safety Society of Nepal, 2021)
Introduction: The job of security guard is to protect the property and the people who reside or work on the premises where they guard. The occupational safety requires the maintenance and the promotion of workers' health and working capacity by improving the working environment and the development of working organizations. The aim of study was to assess the occupational health hazards among the security guards and to find association between occupational health hazards with demographic variables. Methods: A cross-sectional study was conducted among the security guards across Kathmandu district from 20th December 2020 to 8th January 2021 using convenient sampling technique. The data was collected by direct interview method using the structured questionnaire. Results: The mean age of the respondents was 36.5 years with standard deviation 9.54. Males were 88.5 %. Most of the respondents (74%) were married. Majority of the respondents (78%) were Hindu by religion. The prevalence of Muscle pain was 70%, one fifth of the respondents (20%) had lower back pain. The Neck pain, elbow-hand- wrist pain and upper back pain each was present in 10% of the respondents. Conclusion: The muscular pain was not significant difference with demographic variables age, sex, marital status, ethnicity, religion and education status. The muscle pain was found higher in low worked experience of the security guards and not statistically significant.